Pengaruh Environmental Personality dan Sikap Pencegahan Pandemi Covid-19 terhadap Pro-Environmental Behavior Berkaitan Green Architecture - Hakim Hakim; Tri Endangsih (Jurnal Green Growth dan Manajemen Lingkungan, 2021)
The research objective was to analyze and determine the effect of environmental personality and attitudes to prevent the COVID-19 pandemic on pro environmental behavior (PEB) in relation to green architecture. The research used a survey method, the research approach used quantitative with an explanatory format. Data collection techniques used a questionnaire or questionnaire. The calculation of data analysis requirements used the normality test (Kolmogorov-Smirnov) and the homogeneity test (Levene). Analysis of research data using partial and simultaneous regression analysis, correlation test with Pearson product moment correlation, t-test, and the coefficient of determination. The results showed that there was a positive and significant partial effect of Environmental Personality on Pro Environmental Behavior (PEB) related to Green Architecture with a t count of 9,717. The positive and significant partial influence of the COVID-19 Pandemic Prevention Attitude towards Pro Environmental Behavior (PEB) is related to Green Architecture, with a t count of 9.745. The simultaneous influence of Environmental Personality and Attitude to Prevent the COVID-19 Pandemic on Pro Environmental Behavior (PEB) related to a positive and significant Green Architecture with an F count of 62.159. The greatest influence on the COVID-19 Pandemic Prevention Attitude towards Pro Environmental Behavior (PEB) is related to Green Architecture.